1984
DOI: 10.1111/j.1440-1827.1984.tb02195.x
|View full text |Cite
|
Sign up to set email alerts
|

An Electron Microscopic Study of Acute Promyelocytic Leukemia With Chloroma

Abstract: Tumor forming acute promyelocytic leukemia (APL) is rare and only three cases have been documented. However, there are no reports on either the chloromatous character or electron microscopical analysis. The present paper dealt with a light, electron microscopic and histochemical study of the tumor of APL in a 55‐year‐old Japanese male. The tumors found in the anterior mediastinum and right lower extremity. He died from respiratory disturbance and hydrothorax due to obstruction of the pulmonary truncus by the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1984
1984
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Byrd et al (2) reviewed the extramedullary lesions in acute non-lymphocytic leukemia reported since 1965, and cited no APLcase among 154 well documented cases. Wehave also reviewed other literature and found 16 cases of extramedullary disease of APL from 1965 to 1995 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14), and most of them were extramedullary lesions at relapse (3)(4)(5)(6)(7)(8)(9)(10)(11)(12). Several investigators, however, recently described that ATRAmay increase the incidence of extramedullary relapse.…”
Section: Discussionmentioning
confidence: 99%
“…Byrd et al (2) reviewed the extramedullary lesions in acute non-lymphocytic leukemia reported since 1965, and cited no APLcase among 154 well documented cases. Wehave also reviewed other literature and found 16 cases of extramedullary disease of APL from 1965 to 1995 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14), and most of them were extramedullary lesions at relapse (3)(4)(5)(6)(7)(8)(9)(10)(11)(12). Several investigators, however, recently described that ATRAmay increase the incidence of extramedullary relapse.…”
Section: Discussionmentioning
confidence: 99%
“…2y. 40 Several reports have described an association of GS with a translocation t ( 8 2 I ). Among I000 patients in the MRC AML 8 trial.…”
Section: Figure 2 Hande Section Of Lymph Node Revealing Large Neoplastimentioning
confidence: 98%
“…Aside from CD 15, which was observed in 3 B cell tumors With the advent of cytochemical and histochemical methodology in histopathology, it was found that chloracetate esterase and peroxidase activity were typical of primitive myeloid cells and that the presence of these enzymes could be documented via the von Leder and benzidine reactions. 18,26-33 Diagnostic electron microscopy also contributed to further characterization of GS through demonstration of primary granules within the neoplastic cells.2-26-2s,32, [34][35][36] Although these adjunctive pathologic procedures are still useful, they are less effective than immunohistology in identifying cases of tumefactive AML.5,s,9,12,B,37-4S Several prior communications have addressed the immunocytochemical or immunohistochemical identification of GS. 4,5,7-9,12,41-13,47 Others have reported the results of immunologic analyses in flow cytometric settings as well.…”
Section: Immunohistochemical Observationsmentioning
confidence: 99%